PREVALENCE OF FASCIOLOSIS AND DICROCOELIOSIS IN SLAUGHTERED SHEEP AND GOATS IN BAUCHI ABATTOIR, BAUCHI STATE, NORTHEAST NIGERIA - Chongmobmi, Markus; Gamawa, A. A.; Usman, Y.; Nuhu, Y. (FUDMA JOURNAL OF SCIENCES, 2025)
Sheep and goats are a major contributor of protein in the Nigerian livestock industry. Their productivity is greatly hampered by helminths which account for enormous economic losses. In view of this, 420 bile samples were randomly collected from slaughtered sheep (134) and goats (286) in the Bauchi abattoir between the months of January to May 2024. The bile samples were analysed in the laboratory for the presence of fasciola and dicrocoelium parasites. The age, sex and species of the animals were determined using standard procedures. Out of the 420 sheep and goats sampled 90 (21.4%) were positive for fasciolosis and dicrocoeliosis. The infection was highest with Dicrocoelium dendriticum (84.5%) and was least with Fasciola spp (2.2%). There was significant association between infection and species of animals examined (P = 0.047) with higher infection rate seen in sheep than goats. However, age and sex of the sheep and goats sampled did not significantly influence disposition to infection with the parasites (P = 0.682 and 0.551 respectively). Based on overall prevalence (21.4%) obtained in this study it can be concluded that, fasciolosis and dicrocoeliosis are moderately endemic with dicrocoeliosis beng more prevalent than fasciolosis in the study area among slaughtered sheep and goats examined. The infection is more common in sheep than goats in the study area. Therefore, it is recommended that routine and strategic deworming should be intensified particularly for sheep and goats in the Bauchi area.
Keywords: Fasciolosis; Dicrocoeliosis; Sheep; Goats; Abattoir; Bauchi